Microstructure and Dielectric Properties of LPCVD/CVI-SiBCN Ceramics Annealed at Different Temperatures - Li, Jianping (Materials (Basel), 2017)
SiBCN ceramics were introduced into porous Si(3)N(4) ceramics via a low-pressure chemical vapor deposition and infiltration (LPCVD/CVI) technique, and then the composite ceramics were heat-treated from 1400 °C to 1700 °C in a N(2) atmosphere. The effects of annealing temperatures on microstructure, phase evolution, dielectric properties of SiBCN ceramics were investigated. The results revealed that α-Si(3)N(4) and free carbon were separated below 1700 °C, and then SiC grains formed in the SiBCN ceramic matrix after annealing at 1700 °C through a phase-reaction between free carbon and α-Si(3)N(4). The average dielectric loss of composites increased from 0 to 0.03 due to the formation of dispersive SiC grains and the increase of grain boundaries.